Preferensi Konsumen terhadap Kopi Arabika Kintamani di Kedai Kopi Kota Denpasar, Bali - MUHAMMAD, AKBAR ILMAN; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Consumer Preference for Kintamani Arabica Coffee at Coffee Shops in Denpasar City, Bali.  Coffee is a plantation crop that has enormous potential to be developed. The very abundant coffee production in Indonesia is followed by the increasing interest of the Indonesian people to enjoy coffee, especially Arabica coffee. The growing concern of consumers towards processed products and agricultural products is important for producers and coffee shops to find out the attributes preferred by consumers of Kintamani arabica coffee, Denpasar City, Bali. Attributes of taste, flavour, price, and serving technique are considered to represent the characteristics of Kintamani Arabica coffee to get consumer preferences for Kintamani Arabica coffee. This study aims to identify the characteristics of Kintamani arabica coffee consumers in Denpasar City coffee shops, Bali and analyze the attributes that become consumer preferences for Kintamani Arabica coffee in Denpasar City coffee shops, Bali. The location determination method was carried out by purposive method and accidental sampling. The data used are primary data and secondary data. The method of data analysis is descriptive quantitative and conjoint analysis using SPSS 26 for Windows software. The results of the conjoint analysis show that the attributes of Kintamani arabica coffee that are preferred by consumers are sweet taste, soft flavour, low price and pure coffee serving techniques. The value of the highest level of consumer interest sequentially is the attribute of taste, serving technique, price and aroma. From the results of the research that has been done, there are suggestions that can be made, namely to find out more accurate consumer preferences, coffee entrepreneurs or coffee shops can provide products according to the results of the research, coffee shop business actors are advised to maintain taste quality, and are advised to conduct further research about several attributes that have not been studied.